Audit Sistem Informasi Penjualan Pada UMKM MAM Menggunakan Framework Cobit 5 - Zuraidah, Eva; Sulthon, Besus Maula (JURIKOM (Jurnal Riset Komputer), 2022)
Information Technology (IT) has been applied by MAM MSMEs in marketing their products. The application of IT can certainly cause various problems such as what happened to MAM MSMEs, including problematic applications, product delivery accuracy, company human resources in it, and the use of technology that supports sales transactions. Based on these problems, an information system audit was conducted using Cobit 5 which focused on the EDM04 domain Ensure Resource Optimization, APO04 Manage innovation, APO07 Manage Human Resources, BAI08 Manage Knowledge, DSS01 Manage operations, MEA03 Monitor, Evaluate and Assess Compliance with External Requirements. The results of the study indicate that overall, based on the MAM MAM Cobit maturity level, it is at level F or Fully Archived. From the results of the GAP calculation, it was found that for all domains they had not reached the target level and needed improvements as well as improvements. Sales information system audit on MAM MSMEs using all domains has not reached the expected target level. For the calculation of the average maturity level of the six sub domains, namely 1.30 or 130%, which when viewed from the rating scale, it is included in level F, which has reached the Fully achieved value and from the rounding scale of the mapping index the condition of the model capability is at level 1, namely Performed. Process